ISTERI SEBAGAI PENCARI NAFKAH UTAMA: Studi terhadap Perajin Kapuk di Desa Imogiri, Bantul, Yogyakarta - Djazimah, Siti; Habudin, Ihab (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
Islam has expressly regulate the division of tasks and roles between husbands and wives fairly. Although the husband is obliged to provide sustenance for his wife and children, but the family law of Islam does not forbid a wife from helping her husband in making a living with her husband's consent and does not interfere with her obligations as a housewife. There is a wife in a family of craftsmen in the village of Tegal Kembang, Imogiri, Yogyakarta, which acts as the main breadwinners for their families. This article examines the wives who work as the wage earners by using the concept of maqa> s id ash-shari'ah < 'ah. The impact that emerges of the role of the kapok craftsmen woman is more on the impacts that are in positive traits and it is associated with the hajjiy and daruriy needs. The wife who has an income has the economic independence power that can even sustain the needs of the family. Social interactions that occur in kapok craftsmen community, make a strong emotional connection between kapok craftsmen. While the social interaction with the